INVARIANT STATISTICAL CONVERGENCE AND A-INVARIANT STATISTICAL CONVERGENCE - NURAY, F; SAVAS, E (Indian Nat Sci Acad, 1994)
In this paper we introduce the concepts of sigma-statistical convergence and A-sigma-statistical convergence and give some inclusion relations. Also we obtain necessary and sufficient conditions to characterize the matrices that map some related sequence classes into one another.